A randomized control trial of intensive aphasia therapy after acute stroke: The Very Early Rehabilitation for SpEech (VERSE) study. Issue 5 (July 2021) - Godecke, Erin; Armstrong, Elizabeth; Rai, Tapan; Ciccone, Natalie; Rose, Miranda L; Middleton, Sandy; Whitworth, Anne; Holland, Audrey; Ellery, Fiona; Hankey, Graeme J; Cadilhac, Dominique A; Bernhardt, Julie; et al.
Background: Effectiveness of early intensive aphasia rehabilitation after stroke is unknown. The Very Early Rehabilitation for SpEech trial (VERSE) aimed to determine whether intensive aphasia therapy, beginning within 14 days after stroke, improved communication recovery compared to usual care. Methods: Prospective, randomized, single-blinded trial conducted at 17 acute-care hospitals across Australia/New Zealand from 2014 to 2018. Participants with aphasia following acute stroke were randomized to receive usual care (direct usual care aphasia therapy), or one of two higher intensity regimens (20 sessions of either non-prescribed (usual care-plus or prescribed (VERSE) direct aphasia therapy). The primary outcome was improvement of communication on the Western Aphasia Battery-Revised Aphasia Quotient (AQ) at 12 weeks after stroke. Our pre-planned intention to treat analysis combined high intensity groups for the primary outcome. Findings: Among 13, 654 acute stroke patients screened, 25% (3477) had aphasia, of whom 25% (866) were eligible and 246 randomized to usual care ( n = 81; 33%), usual care-plus ( n = 82; 33%) or VERSE ( n = 83; 34%). At 12 weeks after stroke, the primary outcome was assessed in 217 participants (88%); 14 had died, 9 had withdrawn, and 6 were too unwell for assessment. Communication recovery was 50.3% (95% CI 45.7–54.8) in the high intensity group ( n = 147) and 52.1% (95% CI 46.1–58.1) in the usual care group ( n = 70; difference −1.8, 95% CI −8.7–5.0). There was no difference between groups in non-fatal or fatal adverse events ( p = 0.72). Interpretation: Early, intensive aphasia therapy did not improve communication recovery within 12 weeks post stroke compared to usual care.